Pengaruh Kualitas Pelayanan, Kualitas Produk dan Promosi terhadap Kepuasan Konsumen pada Produk “Kopi Dari Hati” di Perumahan Taman Aster Cikarang Barat - Ronaldo Fajar Mardika (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Kopi dari Hati is a famous coffee brand because its franchises can be found in all major cities in Indonesia. Research related to consumer satisfaction is needed. This research is research conducted in the Taman Aster Housing area to look for the influence of service quality, product quality and promotion on consumer satisfaction with the product "Coffee from the Heart" in the Taman Aster housing complex, West Cikarang. The aim of this research is to determine the influence of service quality and product quality. and Promotion of Consumer Satisfaction with "Coffee from the Heart" Products at the Taman Aster Housing Complex, West Cikarang. The results of this research were that it was found that there was a positive influence of service quality and promotion on consumer satisfaction with the "Coffee from the Heart" product at the Taman Aster Housing Complex, Cikarang Barat. Meanwhile, product quality does not have a positive influence on consumer satisfaction with the "Kopi Dari Hati" product at the Taman Aster Housing Complex, Cikarang Barat because this might happen when Kopi Dari Hati customers get the product they ordered that is less than their expectations